INOVASI BISNIS DAN CITRA MEREK KULINER KERIPIK TULANG AYAM “ANEKA RASA MR.BONES” - Herawati Riwu; Angela Karolin; Jessica Hannanda Gracia; Ako Naomi Ratna Puspita; Sepdwipa Mahendra; Yusak Prakoso (Jurnal Kewirausahaan Bukit Pengharapan, 2022)
This research is to prove that product innovation and brand image affects sales in business. The culinary business is growing rapidly in Indonesia. Starup is a new venture and is still in the development stage. Chicken Bone Chips are the result of innovation from the processing of raw materials in the form of chicken bones, which often chicken bones become wasted material. The innovation of chicken bone chips provides added value based on the benefits of wasted products. Chicken bone processing is carried out through several stages, namely the cleaning process, the presto process to become soft bones, the grinding process, the process of making chip dough, the printing process, the frying process, the process of mixing spices and chips, the packaging process. Research on this innovation uses descriptive qualitative. The subjects in this study were consumers of chips from Mr.Bone chicken bones consisting of 20 people. The study was conducted by observation, interview and documentation methods. Data analysis techniques with reduction, display and conclusion. The results of processing chicken bones in the form of chips with various flavors are innovative products that have been interested in by consumers, both children, young and old people. The sale of this chicken bone chip product to all walks of life. Marketing strategies used with digital marketing (instagram, tik tok, facebook, wa, Shopee). Marketing results show customer satisfaction